Aproximación completa del genoma del cáncer de mama basal - Dominguez y Cols., Mev (2019)
Basal like breast cancer (BLBC) composes up to 15% of breast cancer (BC) and is characterized by low or absent expression of estrogen receptor (ER), progesterone receptor (PR), lack of HER2 gene amplification and expression of basal cytokeratins (Cks) 5, 6, 14 and/or 17, epidermal growth factor receptor (EGFR) and/or C-Kit. BLBC constitutes a distinct clinical entity and is associated with poorer clinical outcome (Sørlie et al. 2001). The principal objective of this project is the complete and comparative mapping of genomic abnormalities in a series of BLBC associated or not to BRCA1 mutations and explores the role of the BRCA1 pathway in BLBC. For this reason, we are evaluating a 2.1 M feature human exome capture array on 9 frozen samples obtained from the Pathology Department of Centre Jean Perrin. By the time, we identified on one individual (MCD-4) 11,109 variants, of which 7,113 (64%) were described as known single nucleotide polymorphism (SNP) based on the conservative HCDiff algoritrhm. In regards to the distribution of these variations, chromosomes 10 and 2 were most affected. The novel somatic variations will be confirmed by conventional sequencing. The analyses of the remaining patients are ongoing. Using this next generation methodology, we will contribute to identify new markers or therapeutic targets and help to complete a catalogue of recurrent somatic and inherited variants associated with the development of BLBC.